2013
DOI: 10.1097/pcc.0b013e3182975eee
|View full text |Cite
|
Sign up to set email alerts
|

Is Shock Index Associated With Outcome in Children With Sepsis/Septic Shock?*

Abstract: Shock index may have promise as a marker of mortality in children with sepsis/septic shock. Although there is no clear cutoff shock index to identify risk of mortality, given the higher risk of mortality as shock index increases, children with elevated shock index may benefit from more aggressive resuscitation and higher level of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 10 publications
0
36
1
3
Order By: Relevance
“…Utilizing and the potential benefits of SI as a predictor of mortality and Intensive Care Unit (ICU) admission was evaluated by many other studies as well, and its superiority to conventional vital sign measurements were demonstrated in most of them in pre-hospital and in-hospital settings in trauma and medical patients [20][21][22][23]. However, No study has yet focused on evaluating all of these indices (SI, MSI, and Age SI) in one patient population and comparing them with conventional vital sign measurement and with each other in a specific subgroup of triaged patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Utilizing and the potential benefits of SI as a predictor of mortality and Intensive Care Unit (ICU) admission was evaluated by many other studies as well, and its superiority to conventional vital sign measurements were demonstrated in most of them in pre-hospital and in-hospital settings in trauma and medical patients [20][21][22][23]. However, No study has yet focused on evaluating all of these indices (SI, MSI, and Age SI) in one patient population and comparing them with conventional vital sign measurement and with each other in a specific subgroup of triaged patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…La meta es disminuir el IS, bajando la FC y subiendo la PAS. 12,13 Metas de oxigenación l Obtener una saturación de oxígeno en la vena cava superior (SatO 2vc ) > 70 %. 14 La medición de la saturación de oxígeno en la vena cava inferior (SatO 2vci ) o en la aurícula derecha (SatO 2ad ) también es válida.…”
Section: Metas De Tratamientounclassified
“…Shock index (heart rate/systolic blood pressure) has been proposed as an early marker of disease severity in children with sepsis, and shock index changes in response to therapy as a predictor of clinical outcome . However, variable age‐based cut‐off values between studies and conflicting evidence for identification and prognostication of septic children have limited its clinical utility.…”
Section: Introductionmentioning
confidence: 99%